Study on magnetic field parameters in the inductor working chamber - Nikolay V. Limarenko; Victor P. Zharov; Yury V. Panov; Boris G. Shapoval (Advanced Engineering Research)
The inductor which allows the usage of the magnetic field in the agriculture technological processes is considered. The measuring technique of the electromagnetic field vector characterization - magnetic induction that evaluates the quality of the technological process in the inductor chamber - is offered. Intensity, directivity, and uniformity of the magnetic field in the inductor working chamber are investigated. The techniques of the instrumental, direct and indirect measurements, and statistical data processing, as well as methods of analog-to-digital data conversion are used. A cybernetic model of the experimental research to assess the inductor performance quality is developed. The distribution of the radial and axial components of the magnetic induction in the working chamber is determined; the area with the most uniform magnitude and the magnetic-field direction which forms the inductor working area is identified. The most significant component of the magnetic induction vector for this process and the type of inductor is revealed. The results obtained are important for the development of new inductor constructions.